Studies on the current situation of the Archiepiscopate of Bucharest agricultural partimony - Florin Ungureanu; Ioan Niculae Alecu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The Romanian Orthodox Church, founded as Patriarchy in 1925, performs alongside the pastoral and missionary works specific to the orthodox cult and administrative works. The cult units of the Archiepiscopate of Bucharest, as part of the Metropolitanate of Muntenia and Dobrogea, own agricultural, horticulture and forestry land. The agricultural and horticultural lands are cultivated under own regime or under a lease. For the areas with forest vegetation the cult units have forest service contracts with private or state Forest Districts, specialized inspectors of the Archiepiscopate of Bucharest participating in the sustainable forest management. Vineyards are subject to the reconversion program (by APIA programs) with noble varieties of vineyards and for producing wine it was built a section of vinification , by accessing European funds, with modern technology. The cult units participate in improving the quality of life in rural areas by implementing programs for accessing European funds (job creation, efficient exploitation of land, economic development, strong correlation between the creditworthiness of agricultural land and infrastructure).
Keywords: 330; Archdiocese of Bucharest; agricultural patrimony; horticulture; forestry